2019
DOI: 10.3389/fped.2019.00032
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Risk Factors for Pediatric Kidney Stone Formation: The Effects of Sex

Abstract: Background: Urinary stones are affecting more children, and pediatric stone formers have unique pathophysiology compared to adults. While adult stone formers are most frequently male, children have an age dependent sex prevalence. Under 10 years, a majority of stone formers are boys; adolescent stone formers are mostly female. Previous adult studies have shown that stone composition is influenced by the sex and age of the stone former. Thus, we hypothesize that female and male stone forming children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
2
8
0
1
Order By: Relevance
“…Furthermore, the lifetime risk of developing KSD among females increased by 45% during the study period (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012). Both this study and one by Schwadrerer et al recorded that girls were most likely to experience KSD in adolescence [42,43]. This age group is increasingly affected by KSD which is consistent with findings from NHNES [10].…”
Section: Gender Difference In Paediatricssupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the lifetime risk of developing KSD among females increased by 45% during the study period (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012). Both this study and one by Schwadrerer et al recorded that girls were most likely to experience KSD in adolescence [42,43]. This age group is increasingly affected by KSD which is consistent with findings from NHNES [10].…”
Section: Gender Difference In Paediatricssupporting
confidence: 91%
“…A large contributing factor for this is considered to be the paralleled rise of body mass index (BMI) in this age group [41]. Three studies were identified, which investigated gender differences in paediatric KSD [42][43][44]. Taisan et al reported findings from a longitudinal study over a 30-year period and found the overall risk of KSD doubled in children [42].…”
Section: Gender Difference In Paediatricsmentioning
confidence: 99%
“…The clinical outcome of kidney disease in children is poorly understood. According to a recent report, male and female patients have similar hospitalization rates and frequency of stone episodes [23]. In an older study that attempted to investigate clinical outcomes in children with urolithiasis, the investigators were unable to comment on the outcome of urolithiasis in their patients [21].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of RSD in children has doubled from 7.2 to 14.5/100,000 person-years in the past 2 to 3 decades. [3,4] Colicky abdominal pain is the most common presentation of stone disease (50-80%) followed by non-specific abdominal pain and gross hematuria in 30-50% children. Lower urinary tract symptoms such as frequency, urgency and dysuria, urinary tract infection, urinary retention in case of stone obstructing the urethra, and passage of stones are the other common presentations.…”
Section: Discussionmentioning
confidence: 99%